1994
DOI: 10.1159/000276613
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Alpha-ANP in the Cochlea and the Vestibular Organs

Abstract: The distribution of rat alpha-atrial natriuretic polypeptide (ANP) was studied in the adult inner ear of the Sprague-Dawley rat using immunohistochemical methods. Immunostaining, in particular of the subepithelial stroma cells of the spiral ligament, the spiral prominence and below neuroepithelial areas of all five vestibular organs, was identified. We hypothesize that alpha-ANP is involved in perilymphatic dynamics rather than generating endolymph. The strong staining for alpha-ANP of outer hair cells indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Furthermore, ANP and its receptors have been found in the CNS, leading us to speculate that ANP may function as a neuromodulator or neuropeptide involved in neuronal and glial functions [34][35][36]. Importantly, their presence in the secretory and sensory compartments of the rodent inner ear is well documented, suggesting ANP may act as a local hormone regulating the fluid and electrolyte balance in the inner ear [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Previous reports revealed that ANP receptors have been localized to the cochlear modiolus of the guinea pig [42] and rat SG [51].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ANP and its receptors have been found in the CNS, leading us to speculate that ANP may function as a neuromodulator or neuropeptide involved in neuronal and glial functions [34][35][36]. Importantly, their presence in the secretory and sensory compartments of the rodent inner ear is well documented, suggesting ANP may act as a local hormone regulating the fluid and electrolyte balance in the inner ear [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Previous reports revealed that ANP receptors have been localized to the cochlear modiolus of the guinea pig [42] and rat SG [51].…”
Section: Introductionmentioning
confidence: 99%
“…In the ear, ANP may play a role in maintaining water and/or ion homeostasis of the fluids that are responsible for normal hearing. We previously reported that ANP is present in the rat inner ear by immunohistochemical studies 11, 12. Interestingly, ANP immunoreactivity was detected in the spiral ligament and spiral limbus of the rat cochlea.…”
Section: Discussionmentioning
confidence: 84%
“…Recent studies have revealed extra‐atrial ANP in various tissues 3, 7–10. The presence of ANP in the rat inner ear was first described by Yoon and Hellstrom, who have suggested that it may regulate the volume of perilymph 11, 12. Changes in the volume of perilymph may result in stretching of the surrounding wall, thereby stimulating the secretion of ANP.…”
Section: Introductionmentioning
confidence: 99%
“…The spiral ligament plays an important role in the homeostasis of inner ear fluids, especially the perilymph [24], The specific and intense immunoreactivity for HYA in the spiral ligament along the basal cell layer in the stria vascularis may therefore indicate that HYA acts as a molecular filter against intercellular ionic leakage in addi tion to the sealing of the stria vascularis with tight junc tions towards the lateral wall of the cochlea. A sealing or minimizing of ionic exchange towards all surfaces other than the endolymphatic space will focus the production of energy in the stria vascularis on its main purpose, i.e.…”
Section: Discussionmentioning
confidence: 99%